Pemikiran Munif Chatib dalam Pendidikan Generasi Z Berbasis Multiple Intelligences - Fauzi Misbahul Munir; Apri Eka Budiyono; Ahmad Dawam (CV. Biha Cendekia, 2026)
This study aims to examine Munif Chatib's thoughts on educating Generation Z teenagers through the multiple intelligences approach. Generation Z, as digital natives, grow and develop amid rapid advances in information technology, digital media, and globalization, which have a major influence on their mindsets, behaviors, and learning styles. These conditions demand an educational model that not only emphasizes academic achievement and cognitive intelligence, but also develops the emotional, social, moral, and spiritual aspects of students in a balanced manner. Education oriented towards human values is very important so that Generation Z teenagers do not lose their identity amid the tide of modernization. Through his works such as Sekolahnya Manusia (School of Humans), Gurunya Manusia (Teachers of Humans), and Orangtuanya Manusia (Parents of Humans), Munif Chatib offers a humanistic, contextual, and learner-centered educational paradigm. He emphasizes that every child is born with different uniqueness, intelligence, and talents, so the educational process cannot be standardized. Munif Chatib's thinking is based on the theory of multiple intelligences proposed by Howard Gardner, which states that human intelligence is diverse and unique to each individual. This study uses a descriptive qualitative method with a literature review approach. The results show that the multiple intelligences approach is relevant in the education of Generation Z adolescents because it can encourage character development, creativity, self-confidence, and a balance between academic and non-academic abilities. The role of teachers as facilitators, motivators, and mentors is key to the successful implementation of multiple intelligences-based education. Thus, multiple intelligences-based education can help Generation Z adolescents develop optimally as well-rounded individuals who are intelligent, have good character, and are adaptable to the challenges of the times.